Analisis Indeks Konektivitas dan Aksesibilitas Wilayah Kepulauan: Studi Kasus Kepulauan Maluku dan Papua - Mustakim, Achmad; Nur, Hasan Iqbal; Agustinus, Hoki (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2017)
Inter- regional access by sea transportation is not yet optimal. The cause of the unoptimality of sea transportation are the imbalance cargo between Eastern Indonesia and Western Indonesia and also the port infrastructures. This research aims to calculate connectivity index in Maluku Archipelago. Connectivity index can be represented by degree connectivity and port accesibility index. Degree connectivity is connectivity degree between the ports. Port accesibility index is a degree that represented the capacity of port. Then Granger causality are applied to know a region is “Transport Follow the Trade”or “Trade follow the transport”. Then find the way to increase the connectivity index. The results of the research are the highest connectivity index is Sorong Port. Sorong port has result 9 for container cargo and 18 for general cargo. The highest accesibility index are Jayapura port (container cargo) and Sorong Port (general cargo) with index value is 1. Granger causality test. Granger causality test results show "Transport Follow The Trade" in West Papua and Papua Province with probabilities of 0.86 and 0.27 respectively on container cargo, 0.50 and 0.37 on general cargo. "Transport Promote The Trade" is suitable in the Province of North Maluku and Maluku with probabilities of 0.65 and 0.43 respectively on container cargo 0.85 and 0.52 on the general cargo. At the rate of GDP of 3% per year, the accessibility of container loading in Jayapura Port increased 1.6% to 505 TEUs / day, and the growth rate of GDP in Maluku Province by 5% per year accessibility of cargo general cargo at Ambon Port increased 12% or 752 tons / day.